THE EXERCISE ASTHMA THREE TIMES A WEEK MORE INCREASE FORCED VITAL CAPACITY (KVP) AND FORCED EXPIRATORY VOLUME IN 1 SEC (VEP 1) OF ONCE A WEEK IN MODERATE PERSISTENT ASTHMA PATIENTS - Darmayasa, I Ketut (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 1 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i01.p04)
Objective: This study aims to determine the difference giving the frequency of asthmaexercise three times a week with once a week to improved Forced Vital Capacity (KVP), forcedexpiratory volume in 1 second (VEP 1) in patients with persistent asthma were measured usingSpirometry. Methods: The study was conducted with the design of pre test and post test groupdesign. Sampling Purposive sample taken with the inclusion criteria, exclusion. Samples weredivided into 2 groups, each group numbering 12 people. Group I will be given the treatment ofasthma gym three times a week in patients with persistent moderate asthma, exercise asthma group II are given once a week. Results: Data were analyzed by Test Paired sample t-testshowed that each group produces an increase in the VEP, and KVP before and after treatmentwere significantly different (p <0.05). While the Independent sample t-test test aimed to comparethe two treatment groups for VEP 1, KVP shows that the value (p <0.05). This means showingsignificant differences between the two treatments to increase VEP 1, KVP. Conclusion: Thismeans it can be concluded that asthma exercise three times a week is better than the gym once aweek to improved asthma Kapasital Forced Vital (KVP), forced expiratory volume in 1 second(VEP 1) in patients with persistent moderate asthma.
Keywords: Exercise asthma, Forced Vital Capacity (KVP), Forced expiratory volume Seconds 1 (VEP 1)